Scienze sociali e progetto di territorio - PICONE, Marco (FrancoAngeli, 2012)
Which role can social sciences play in the creation of a territorial project? Can social scientists contribute to a wider picture of ecosustainable development? Starting from these key questions, the present chapter tries to summarize the different approaches that define the presence of social scientists in planning processes, focusing mainly on the fundamental idea of landscape. By employing Dematteis’s suggestion of a ‘Northwest Passage’ enabling to fully understand what landscapes are, social scientists become the key link between scholars with different expertise and formation. Furthermore, this chapter reflects on quantitative and qualitative methodologies, suggesting that both must be employed to improve the social scientists’ toolbox, but it also hints that qualitative and participative methodologies may grant particularly useful results. Two case studies (the guidelines for the Sicilian Piano Territoriale Paesistico Regionale and the interpretative plan for the Parco del Matese) prove how social scientists may play a significant role in participative planning, but only if ethics and social justice become the intellectual framework of their agenda.